A morphologic and histologic study of the radial nerve and its branches at potential compression sites. Issue 5 (October 2020) - Nair, Shreya; Ankolekar, Vrinda H.; Hosapatna, Mamatha; DSouza, Anne
الملخص: أهداف البحث: بحثت هذه الدراسة في الاختلاف في مستوى انتهاء العصب الكعبري، والقياس الشكلي للعصب الكعبري، وفروعه في مواقع الضغط المحتملة. بالإضافة إلى ذلك، قمنا بتحليل رقمي لمقاطع نسيجية للعصب الكعبري، والفرع السطحي للعصب الكعبري والعصب بين العظام الخلفي. طرق البحث: أجرينا هذه الدراسة على ١٤ جثة لبالغين محفوظة بالفورمالين. تم قياس أطوال العصب الكعبري، والفرع السطحي للعصب الكعبري والعصب بين العظام الخلفي إلى أن يصل إلى مواقع الضغط المحتملة باستخدام المعالم السطحية الهيكلية المناسبة كنقاط مرجعية. نسيجيا، قمنا بتقييم المناطق ذات الحزم وغير ذات الحزم وعدد المحاور لكل عصب. تم تحليل جميع المعلومات إحصائيا. النتائج: وجدنا اختلافا في انقسام العصب الكعبري بالنسبة إلى خط ثنائي اللقيمات. ولكن الفروع الطرفية للعصب الكعبري لها مسار ثابت في الساعد. نسيجيا، كان هناك اختلاف كبير بين المناطق ذات الحزم وغير ذات الحزم للعصب بين العظام الخلفي. لم يكن هناك اختلاف جذري بين المحاور العصبية الكلية للفرع السطحي للعصب الكعبري والعصب بين العظام الخلفي. أخيرا، لاحظنا أن هناك اختلاف في الطول العضلي للعصب بين العظام الخلفي داخل العضلة الضاغطة، وأن لدى الفرع السطحي للعصب الكعبري أكبر عدد من الحزم بالمقارنة بالعصب الكعبري والعصب بين العظام الخلفي. الاستنتاجات: في هذه الدراسة، لدى العصب الكعبري والعصب بين العظام الخلفي قياس متغير أكثر بالمقارنة بالفرع السطحي للعصب الكعبري. يوفر التقييم النسيجي ومقاييس هذه الأعصاب في مواقع الضغط المحتملة دليلا للجراحين لتخطيط إجراءات إعادة بناء الأعصاب. Abstract: Objectives: This study examined variations in the termination level of the radial nerve (RN) and the morphometry of the RN and its branches at potential compression sites. Additionally, we digitally analysed histological sections of the RN, the superficial branch of the radial nerve (SBRN), and the posterior interosseous nerve (PIN). Methods: We conducted this study on 14 formalin fixed adult cadavers. The lengths of the RN, SBRN, and PIN were measured up to potential compression sites, using appropriate surface skeletal landmarks as reference points. We histologically evaluated the fascicular and non-fascicular areas and the number of axons in each nerve. All parameters were statistically analysed using a paired t-test. Results: We found variations in the bifurcation of the RN with respect to the biepicondylar line (BEL). However, the course of RN terminal branches was constant in the forearm. There was a significant histological difference between the fascicular and non-fascicular areas of the PIN. There was no significant difference in the total number of axons in the SBRN and PIN. Finally, we observed that the intramuscular length of the PIN within the supinator muscle was variable and that the SBRN had more fascicles compared to the RN and PIN. Conclusions: In our study, the RN and PIN had more variable morphometry compared to that of the SBRN. The histologic evaluation and quantification of these nerves at their potential compression sites could serve as a guide for surgeons planning nerve reconstruction procedures.